That's so good they don’t give so much? The Colombian experience in land formalization in light of international evidence [¿De eso tan bueno no dan tanto? La experiencia colombiana en formalización de tierras a la luz de la evidencia internacional (2019)
Since the 1990s, Colombian governments have invested in the formalization of land tenure rights seeking to promote development, stimulate the land market and improve the living conditions of rural dwellers. However, the relationship between the formalization and the promises made on its behalf is not entirely clear since international experiences show that the positive effects of these programs appear under certain conditions that are often overlooked by decision makers. The purpose of this paper is to reflect on the progress and setbacks of the land tenure formalization programs in Colombia in the light of the review of academic and policy debates on property rights. This research allows us to show some implications about the future of land policies and the importance of the implementation of Integral Rural Reform as part of the Peace Agreement. © 2019, Universidad Nacional de Colombia. All rights reserved.